2021
DOI: 10.1590/1806-9282.20210198
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen-to-albumin ratio may be a predictor for ascending aortic aneurysm

Abstract: OBJECTIVE:The predictive value of the fibrinogen-to-albumin ratio has been evidenced in coronary artery disease. Available data demonstrated that inflammation and oxidative stress are the relevant mechanisms of ascending aortic aneurysm formation and dilatation.The fibrinogen-to-albumin ratio reflects oxidative stress and inflammation. This study investigated the correlation between fibrinogento-albumin ratio and ascending aortic aneurysm.METHODS: A total of 250 consecutive patients with ascending aortic aneur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Furthermore, the present study identified a higher fibrinogen to albumin ratio as a novel independent and additional predictor of intrahospital mortality in neurosurgical ICU patients with ICH. The fibrinogen to albumin ratio was commonly identified as a predictor of poor outcome and adverse events in patients with cardiovascular diseases, cancer, sepsis, and stroke, although not in neurosurgical ICU-admitted ICH patients [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. This is the first report on the impact of the fibrinogen to albumin ratio in neurosurgical ICU patients with ICH, and it presents a significant association of intrahospital mortality and a fibrinogen to albumin ratio >0.075 upon admission.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, the present study identified a higher fibrinogen to albumin ratio as a novel independent and additional predictor of intrahospital mortality in neurosurgical ICU patients with ICH. The fibrinogen to albumin ratio was commonly identified as a predictor of poor outcome and adverse events in patients with cardiovascular diseases, cancer, sepsis, and stroke, although not in neurosurgical ICU-admitted ICH patients [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. This is the first report on the impact of the fibrinogen to albumin ratio in neurosurgical ICU patients with ICH, and it presents a significant association of intrahospital mortality and a fibrinogen to albumin ratio >0.075 upon admission.…”
Section: Discussionmentioning
confidence: 99%
“…However, both biomarkers, fibrinogen and albumin, are synthesized in the liver, so the prognostic value of these single biomarkers alone is limited in patients with hepatic insufficiency (e.g., cancer, malnutrition, or chronic heart failure). On this account, a new biomarker, the fibrinogen to albumin ratio, was implemented to determine medical conditions including malnutrition, coagulation system, systemic inflammation, and hepatic insufficiency [ 20 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations